1990
DOI: 10.1016/0140-6736(90)90001-l
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's sarcoma among persons with AIDS: a sexually transmitted infection?

Abstract: In the United States Kaposi's sarcoma is at least 20,000 times more common in persons with acquired immunodeficiency syndrome (AIDS) than in the general population and 300 times more common than in other immunosuppressed groups. Among persons with the acquired immunodeficiency syndrome (AIDS) reported to Centers for Disease Control by March 31, 1989, 15% (13,616) had Kaposi's sarcoma. Kaposi's sarcoma was commoner among those who had acquired the human immunodeficiency virus (HIV) by sexual contact than parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
419
2
25

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 978 publications
(458 citation statements)
references
References 26 publications
12
419
2
25
Order By: Relevance
“…Four major clinical forms have since been described [Giraldo et al, 1989;Martin et al, 1993]: (1) epidemic or acquired immunodeficiency syndrome AIDS-associated; (2) classic; (3) African endemic; and (4) immunosuppressionassociated (iatrogenic) Kaposi's sarcoma [Giraldo et al, 1989;Beral et al, 1990;Martin et al, 1993]. African endemic Kaposi's sarcoma clusters among Africans from East and Central Africa and accounts for 3-18% of all malignancies in these regions [Martin et al, 1993;Gompels and Kasolo, 1996;Lennette et al, 1996;Kasolo et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Four major clinical forms have since been described [Giraldo et al, 1989;Martin et al, 1993]: (1) epidemic or acquired immunodeficiency syndrome AIDS-associated; (2) classic; (3) African endemic; and (4) immunosuppressionassociated (iatrogenic) Kaposi's sarcoma [Giraldo et al, 1989;Beral et al, 1990;Martin et al, 1993]. African endemic Kaposi's sarcoma clusters among Africans from East and Central Africa and accounts for 3-18% of all malignancies in these regions [Martin et al, 1993;Gompels and Kasolo, 1996;Lennette et al, 1996;Kasolo et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is evidence that classical KS was increasing before the AIDS epidemic, with a doubling of incidence in Sweden over 25 years before 1982 (Dictor andAttewell, 1988). In the USA there is now a consistent decrease in the incidence of AIDS-KS (Beral et al, 1990), with a 4-fold fall among a cohort of homosexual men with AIDS between 1983(Katz et al, 1994 Huang et al, 1995;Boshoff et al, 1995;Dupin et al, 1995;Moore and Chang, 1995;Lebbe et al, 1995;Schalling et al, 1995). The agent was also identified in African endemic KS (Huang et al, 1995;Lebbe et al, 1995;Schalling et al, 1995).…”
Section: Epidemiologymentioning
confidence: 96%
“…Analysis of 13 000 persons with AIDS reported to the Centres for Disease Control, Atlanta, GA, USA, up to 1989 revealed that the incidence of KS in homosexual and bisexual men infected with HIV is ten times greater than in other seropositive transmission groups (Beral et al, 1990). The lifetime incidence in some cohorts of homosexual men with AIDS is 50% (Katz et al, 1994).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of developing KS for untreated AIDS patients is estimated to be 300 times greater than that of other immunosuppressed individuals and 20 000 times greater that of the general population. 18 In this group, KS frequently assumes an aggressive course. Areas prone to KS in the adult AIDS population include: the oral cavity, especially the hard palate, the tip of the nose, behind the ears, the trunk, penis, legs, and feet.…”
Section: Kaposi Sarcomamentioning
confidence: 99%